Discrimination of Prion Strain Targeting in the Central Nervous System via Reactive Astrocyte Heterogeneity in CD44 Expression - Bradford, Barry M.; Wijaya, Christianus A. W.; Mabbott, Neil A. (Frontiers in Cellular Neuroscience, 2019)
Prion diseases or transmissible spongiform encephalopathies are fatal, progressive, neurodegenerative, protein-misfolding disorders. Prion diseases may arise spontaneously, be inherited genetically or be acquired by infection and affect a variety of mammalian species including humans. Prion infections in the central nervous system (CNS) cause extensive neuropathology, including abnormal accumulations of misfolded host prion protein, vacuolar change resulting in sponge-like (spongiform) appearance of CNS tissue, neurodegeneration and reactive glial responses. Many different prion agent strains exist and these can differ based on disease duration, clinical signs and the targeting and distribution of the neuropathology in distinct brain areas. Reactive astrocytes are a prominent feature in the prion disease affected CNS as revealed by distinct morphological changes and upregulation of glial fibrillary acidic protein (GFAP). The CD44 antigen is a transmembrane glycoprotein involved in cell-cell interactions, cell adhesion and migration. Here we show that CD44 is also highly expressed in a subset of reactive astrocytes in regions of the CNS targeted by prions. Astrocyte heterogeneity revealed by differential CD44 upregulation occurs coincident with the earliest neuropathological changes during the pre-clinical phase of disease, and is not affected by the route of infection. The expression and distribution of CD44 was compared in brains from a large collection of 15 distinct prion agent strains transmitted to mice of different prion protein (Prnp) genotype backgrounds. Our data show that the pattern of CD44 upregulation observed in the hippocampus in each prion agent strain and host Prnp genotype combination was unique. Many mouse-adapted prion strains and hosts have previously been characterized based on the pattern of the distribution of the spongiform pathology or the misfolded PrP deposition within the brain. Our data show that CD44 expression also provides a reliable discriminatory marker of prion infection with a greater dynamic range than misfolded prion protein deposition, aiding strain identification. Together, our data reveal CD44 as a novel marker to detect reactive astrocyte heterogeneity during CNS prion disease and for enhanced identification of distinct prion agent strains.